Analysis of Rainfall as an Agroclimatological Element on Production and Determination of Potato (Solanum Tuberosum L.) Planting Season in South Tapanuli Regency - Syawaluddin; Imelda Sari Harahap; Hery Solat (Formosa Journal of Sustainable Research, 2023)
Rain is a very important factor in the availability of water for planting. Farmers still use the traditional way of determining the planting schedule. This determination is considered less than optimal. This study aims to analyze rainfall on potato production in South Tapanuli Regency based on rainfall data, and determine the relationship between rainfall and the suitability of sweet potato crops. The research method used is a survey method and literature review. This type of research is a survey method with a correlation and descriptive approach to see the relationship between rainfall and potatoes used with correlation. From this research, the results of correlation and regression analysis of the rainfall variable on the potato productivity variable for the last 10 years were obtained from the Central Bureau of Statistics for South Tapanuli Regency, which illustrates a weak positive effect